Human Bites Over Nose: Management and Reconstruction - Singh, Kuldeep; Aggarwal, Krittika (Archives of Plastic Surgery, 2023)
Background Human bite wounds in emergency department need evaluation in regard of reconstruction. These are due to occlusive bite injuries over face. Most commonly, human bites over face involve ear and nose, and may lead to avulsion injury. Defects over nose can be reconstructed immediately after debridement or delayed till the wound heals and scar becomes supple. Thorough wash and lavage with broad- spectrum antibiotic cover has utmost importance in preventing cartilage infection.Methods We report 20 cases of human bite injuries over nose who presented to us in emergency department between 2018 and 2020. At the time of presentation the wound was assessed for closure. If not possible, patient was planned for delayed reconstruction after 3 months. In case delayed reconstruction was planned, the skin and nasal mucosa were approximated at first presentation. The patients underwent paramedian forehead flap after recreation of defect with conchal cartilage graft. Second stage of flap detachment and insetting was done after 3 weeks. After three weeks of second stage, third stage of flap thinning was done. Patients were followed for 3-6 months and subjective satisfaction was noted.Results Nineteen patients underwent delayed staged reconstruction with paramedian forehead flap and one underwent primary wound closure. The flap survival was 100%. The patient satisfaction was excellent in most cases.Conclusion We recommend delayed reconstruction for human bite nasal injuries. For reconstruction, paramedian forehead flap with conchal cartilage graft, if required, provides excellent reconstructive option with good contour and color match and minimal donor site scar.
Keywords: human bite nose; reconstruction; forehead flap